2000
DOI: 10.1029/1999ja900476
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of HF‐enhanced plasma and ion lines at EISCAT with high‐altitude resolution

Abstract: Abstract. Measurements of plasma and ion lines induced during HF ionospheric interaction experiments have been made with the European Incoherent Scatter (EISCAT) facility at TromsO with sufficiently high-altitude resolution to compare with theories of Langmuir turbulence. Recent Langmuir turbulence models predict a change from broad structureless spectra to line or cascade spectra within a few hundred meters for VHF (224 MHz) observations assuming typical ionospheric density gradients. In a campaign in May 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 31 publications
8
78
0
Order By: Relevance
“…Figure 7 is reproduced from Wright et al (2006) and shows a typical example of hysteresis identified in ionospheric electron temperatures within the heated volume observed over Tromsø using the EISCAT UHF radar, over a height range which encompasses that where the artificial FAI are generated (the upper-hybrid height, as identified using the ion-line overshoot effect; e.g. Rietveld et al, 2000). Similar hysteresis was observed in changes in electron density induced by the heating effect.…”
Section: Discussionmentioning
confidence: 60%
“…Figure 7 is reproduced from Wright et al (2006) and shows a typical example of hysteresis identified in ionospheric electron temperatures within the heated volume observed over Tromsø using the EISCAT UHF radar, over a height range which encompasses that where the artificial FAI are generated (the upper-hybrid height, as identified using the ion-line overshoot effect; e.g. Rietveld et al, 2000). Similar hysteresis was observed in changes in electron density induced by the heating effect.…”
Section: Discussionmentioning
confidence: 60%
“…These ionacoustic and Langmuir waves can be detected in the interCorrespondence to: R. S. Dhillon (rsd6@ion.le.ac.uk) action region by radars pointing in a wide range of directions, including those close to the geomagnetic field direction (e.g. Stubbe et al, 1992;Kohl et al, 1993;Djuth et al, 1994;Isham et al, 1999;Honary et al, 1999;Rietveld et al, 2000;Dhillon and Robinson, 2005). These wave modes give rise to enhancements in both the E-and F-region ion and plasma line incoherent scatter spectra.…”
Section: Introductionmentioning
confidence: 99%
“…For the following investigation, electron density profiles provided by the EISCAT UHF radar were used to estimate a value of the upper hybrid height, h U . In these EISCAT UHF data a heater-induced ionline overshoot occurs at the altitude where the plasma frequency is equal to the heater frequency, causing an apparent enhancement in the electron density [Jones et al, 1986;Rietveld et al, 2000]. The height difference, Dz, between this altitude level and the upper hybrid level, U, can be determined, and Rietveld et al [1993] state a typical value of 6 km.…”
Section: Eiscat Uhf Radarmentioning
confidence: 99%